Honey bee colony losses and causes during the active beekeeping season 2022/2023 in nine sub- Saharan African countries - Nganso, B.T.; Ayalew, W.; Wubie, A.J.; Assefa, F.; Belayhun, L.; Ndungu, N.N.; Toroitich, D.; Otieno-Ayayo, Z.N.; Wambua, M.B.; Oyieyo, Y.O.; Elie, N.; Sikirou, R.; et al. (2025)
This study reports for the first-time managed honey bee colony loss rates and associated risk factors during the active beekeeping season 2022/2023 in nine Sub-Saharan African countries, namely Kenya, Ethiopia, Rwanda, Uganda, Benin, Liberia, Nigeria, Cameroon and Democratic Republic of the Congo. The sustainability of bee swarm catches as a main honey bee colony source tool for operation expansion by African beekeepers was also evaluated in Kenya and Ethiopia. In this survey, the 1,786 interviewed beekeepers across these countries collectively managing 41,761 colonies registered an overall loss rate of 21.3%, which varied significantly among countries (from 9.7 to 45.3%) and hive types (from 10.6% in hives with movable frames to 17.9% in frameless hives). The perceived causes of losses in order of significance were issues beyond the beekeeper’s control (mainly theft, drought, and bushfire), absconding and pests (mainly wax moth, small and large hive beetles, ants and Varroa destructor mite), but this pattern varied greatly across countries. Among the management practices and characteristics, migratory operations and professional beekeepers experienced lower losses than stationary operations and semi-professionals and hobby beekeepers. Insights into the number of bee swarms caught revealed significant decreases in swarm availability over the past three years in Kenya. The opposite situation was observed in some regions of Ethiopia. These trends require further investigation. Overall, this comprehensive survey sheds light on the complexities and challenges beekeepers faced in Sub-Saharan Africa, pointing to the need for targeted interventions and sustained research to support the resilience and growth of the apicultural sector.